HİZMETKÂR LİDERLİK, İŞE YÖNELİK TUTUM VE İŞTEN AYRILMA NİYETİ ARASINDAKİ İLİŞKİ: ŞIRNAK ÖRNEĞİ - Ece, Süreyya (Business and Management Studies: An International Journal, 2019)
Employees are the key to the success of businesses. The more positive the attitudes of employees towards their jobs, the more they do not want to leave. In thatcase they can focus more ontheir work andcontribute more to the objectives of thefirm.It is thought that a management that provides services, not only support to employees, will affect the employees' attitudes towards work. In this study, the concept of servant leadership, which provides concrete support for the employees to do theirjob better, is discussed. The effect of employees' servant leadership perceptions on their attitudes towards work is examined. The study also investigateshow the attitudes of employees towards work affect the intention to quit. The questionnaire preparedwithin this scope was applied to private sector employees in Şırnak province. According to the results, there was a positive relationship between servant leadership and the attitude towards the work itself, working conditions and attitudes towards colleagues. A negative relationship was also found between the attitude towards work and intention to quit.
Keywords: Servant Leadership; Attitude Towards Work; Intention To Leave